Impact of the newly proposed ICRU/ICRP quantities on neutron calibration fields and extended range neutron rem-counters. (21st August 2019) - Pozzi, Fabio; Ferrarini, Michele; Ferrulli, Francesca; Silari, Marco
Abstract: In July 2017, the International Commission on Radiation Units and Measurements (ICRU) and the International Commission on Radiological Protection (ICRP) proposed the introduction of new operational quantities for external radiation exposure, with the aim of improving coherence between protection quantities and operational quantities within the system of radiological protection. A change in operational quantities will impact both instrumentation and reference radiation fields used for their calibration. This paper evaluates the potential impact of the new quantity ambient dose, H *, meant to replace ambient dose equivalent, H *(10), on two neutron reference fields, the Am-Be source and the CERF high-energy workplace field, and on the response of two models of extended-range neutron rem counters (LINUS and LUPIN). The conclusions are that calibration procedures should in general not be affected and that changes should only be expected in calibration coefficients. Considering the acceptable measurement uncertainties for operational radiation protection, for the extended-range rem counters changes in their design would not be required for measurements outside particle accelerators shielding and for aircrew dosimetry. One can expect that this type of instrument can still be calibrated with Am-Be source neutrons and employed in neutron fields with energy distributions spanning several decades. For uses in radiation fields with very peculiar neutron energy distribution, a specific workplace field calibration may instead be required.